Diseño de un Sistema para el Control de Costos en la Construcción de Subestaciones - Muñoz-Calvo, Wilberth (Instituto Tecnológico de Costa Rica, 2010)
The work done is the "Cost Control System Design for Construction of Substations", which involves creating a system that allows control of costs under the accounting code structure used by the Instituto Costarricense de Electricidad. To achieve the stated objectives was carried out a preliminary study of all documentation and construction plans with the ICE makes the implementation and monitoring of such projects. Then relate the activities planned for the project under the code ST Garita accounting through the development of work breakdown structure using the program WBS Chart Pro. There were talks by induction on the construction, maintenance and commissioning of substations as well as training on the software used (Visual Studio .Net and Microsoft Access) to create the system to control costs. It is then begun to programming and design of each of the forms and sections that comprise the system. The work ends with the program's inception Cost Control System, which allows a daily cost control through the introduction of information labor, materials, machinery and equipment, which generate reports with useful information for the engineer.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Construcción; Planos; Costos; Material; Ducto